Mário de Andrade e o patrimônio: conceitos e propostas formulados pelo intelectual modernista (1919-1945) - Mariana Sousa Bracarense (2014)
In Brazil, the emergence of practices for protecting cultural heritage took place in the first decade of the twentieth century. Among other propositions, its constitution included the collection of documents about colonial architecture, the warning about the need to preserve the heritage of old towns from Minas Gerais, and also the protection of archaeological sites established by a law draft in 1920. The synthesis of this process occurred through the law draft written by Mário de Andrade, which generated the Decree-Law No. 25 of 30 November 1937, responsible for regulating the Serviço do Patrimônio Histórico e Artístico Nacional - SPHAN. This research investigates the particularities of the emergence of these practices in this country between the years 1919 and 1945. It addresses the elaborations of the concept of heritage by Mário de Andrade in his texts and letters, its use by Modernists and subsequently by the institutional framework of Getúlio Vargass government. Moreover, it intends to understand how the speech on equity was used as a projection of a wishing society. Finally, it articulates the different perspectives addressed in order to think about how the establishment of categories of treatment for culture has influenced the development of the social function of the intellectual by Mário de Andrade.